Environmental Carrying Capacity Based on Ecosystem Services for Settlement Development Plans in The Sota State Border Area, Merauke - Santoso, Dian Hudawan; Astanti, Yuli Dwi; Adventri Wibowo, Astrid Wahyu (Universitas Negeri Medan, 2025)
Sustainable settlement design necessitates the incorporation of environmental carrying capacity determined by ecosystem services. In border areas like the Sota Border Area (KPN) in Papua, ecological pressures intensify as a result of population expansion and economic endeavours. This study assesses the environmental carrying capacity and resilience of settlements through an ecosystem services framework, comparing conditions in 2019 and 2024 to evaluate the impact of development plans. The analysis focuses on five key ecosystem services: food provision, clean water supply, water flow regulation and flood control, disaster protection, and air quality maintenance. Data collection involved field surveys, remote sensing, and GIS-based spatial overlay analysis to map land use changes and ecosystem service values. Results in 2019 showed residential development concentrated in zones with high ecosystem service values, such as food provision (771.7 ha in SUB BWP 2) and clean water supply (742.98 ha in SUB BWP 3). Development in low-lying areas prioritized flood regulation (460.1 ha in SUB BWP 1) and disaster protection (560.7 ha in SUB BWP 1). By 2024, developed land in the very high clean water supply zone of SUB BWP 1 increased sharply from 0.10 ha to 28.86 ha. This research highlights the critical need to incorporate ecosystem service data into settlement planning to sustain environmental capacity and enhance border region sustainability